ASSOCIATION OF PIGMENTED PARAVENOUS RETINOCHOROIDAL ATROPHY WITH A PATHOGENIC VARIANT IN THE HK1 GENE. Issue Volume 16:Issues 6(2022) (November 2022) - Shah, Saumya M.; Schimmenti, Lisa A.; Chiang, John; Iezzi, Raymond
Abstract : This case describes the occurrence of pigmented paravenous retinochoroidal atrophy in a patient with an autosomal dominant pathogenic variant of the hexokinase 1 gene. Abstract : Purpose: To report a case of pigmented paravenous retinochoroidal atrophy in a patient that was found to have an autosomal dominant pathogenic variant of the hexokinase 1 ( HK1 ) gene. Methods: A case report. Results: A 41-year-old White woman with a distant family history of retinitis pigmentosa presented with a 5-year history of bilateral blurry and decreased vision that led to eventual loss of ability to drive. Color funduscopic photographs revealed retinochoroidal atrophy, hyper-reflective spots within the retina, and a paravenous distribution of pigment bilaterally. Given the patient's familial ocular history and workup, she was diagnosed with inherited retinal degeneration with phenotype suggestive of pigmented paravenous retinochoroidal atrophy. Genetic testing revealed a single rare variant, c.2551 G>A in the HK1 gene. Discussion: This case describes a pathogenic variant in HK1, a gene that has been associated with RP, but has not been previously reported in association with the pigmented paravenous retinochoroidal atrophy phenotype. This expands the phenotypes associated with HK1 pathogenic variant, p.Glu851Lys, and the genetic association of pigmented paravenous retinochoroidal atrophy to include HK1 . Although pigmented paravenous retinochoroidal atrophy has been previously reported to be associated with CRB1 gene, no previous relationship to the HK1 gene has been described.